المشكل الوارد في أحاديث القتل ودرءه جمعا ودراسة - قدورة, عبد القادر (جامعة الوادي university of eloued, 2023)
" الحمدلله العالمين، والصلاة والسلام على أشرف الأنبياء والمرسلين، نبينا محمد وعلى آله وصحبه أجمعين، وبعد: فإن هذا البحث يدرس الأحاديث التي فيها الأمر بالقتل ويجيب على الإشكالات التي تعتريها، وحتى الوصول إلى هذا الهدف، فقد قسمت البحث إلى مقدمة ومبحث تمهيدي وثلاث مباحث أساسية وخاتمة. افتتحت بمقدمة بينت فيها الأسباب التي دفعتني لاختيار هذا الموضوع والأهداف المبتغاة منه، كما وضحت فيها المنهجية التي سرت عليها خلال بحثي في الكتابة والتهميش..... ثم شرعت في المبحث التمهيدي الذي تطرقت فيه لدراسة البحث من الجانب النظري، فعرفت الحديث وكذلك عرفت القتل وذكرت أنواعه، كما أوضحت المقصود من مشكل الحديث وذكرت الطرق لدرءه عن الأحاديث. وأما بقية المباحث فقد خصصتها للدراسة التطبيقية، ففي المبحث الأول والثاني درست الأحاديث التي بها الأمر بالقتل حدا بسبب الكفر وبسبب الكبائر، وأجبت على الإشكالات الواردة فيها، وفي المبحث الثالث درست الاحاديث التي فيها الأمر بالقتل لأسباب متنوعة كما أجبت على الإشكالات التي اعترتها. ثم ختمت هذا البحث بخاتمة احتوت أهم النتائج التي توصلت إليها، وبعض التوصيات التي أوصيت بها، وذيلته بعدد من الفهارس حتى يسهل الانتفاع به والاستفادة منه""Praise be to Allah, the Lord of the worlds, and peace and blessings be upon the most honorable prophets and messengers, our Prophet Muhammad and upon all his family and companions, and after: This research examines the hadiths in which the order to kill is given and answers the problems that beset it, and in order to reach this goal, I have divided the research into an introduction, an introductory research, three basic research and a conclusion. I opened with an introduction in which I explained the reasons that motivated me to choose this topic and the goals I wanted from it, and also explained the methodology that I followed during my research in writing and marginalization…. Then I started the preliminary research, in which I discussed the study of research from the theoretical side, so I knew Hadith, as well as I knew murder, mentioned its types, and also explained the purpose of the problem of Hadith and mentioned ways to ward it off from hadiths. As for the rest of the detectives, I devoted it to Applied study, studied the hadiths in which the order to kill was a limit because of disbelief and answered the problems I encountered. Then I concluded this research with a conclusion that contained the most important findings I reached, some of the recommendations I recommended, and it was followed by a number of indexes so that it would be easy to use and benefit from it. "
حديث
Keywords: المشكل... الإشكالات... القتل; The problem...the problems...the killing